The poly‐cistronic expression of four transcriptional factors (CRX, RAX, NEURO‐D, OTX2) in fibroblasts via retro‐ or lentivirus causes partial reprogramming into photoreceptor cells. (20th February 2018) - Fukuda, Tomokazu; Ishizawa, Yasushi; Donai, Kenichiro; Sugano, Eriko; Tomita, Hiroshi
Abstract: The introduction of four key transcriptional factors (CRX, RAX, NEURO‐D, OTX2) allows the direct differentiation of fibroblasts to retinal photoreceptor cells. This reprogramming was achieved with a combination of mono‐cistronic viruses. Although the combination of mono‐cistronic viruses was useful, a relatively high titer of recombinant viruses was necessary because co‐infections are required. To overcome this issue, we established a poly‐cistronic expression system for direct reprogramming and analyzed the biological characteristics of introduced cells after the exogenous introduction. The coding region of four reprogramming factors and EGFP (CRX, RAX, NEURO‐D, OTX2, and EGFP; CNROE) was inserted into multiple sites of the pMYs‐IP retrovirus or CSII‐CMV lentivirus vector. The recombinant viruses were exposed to HE16 human embryonic fibroblasts. The expression levels of cone related genes were detected with real‐time PCR. We detected the activation of two of the photoreceptor‐related genes after the poly‐cistronic expression of CRX, RAX, NEURO‐D, and OTX2, but the rest of the genes did not exhibit transcriptional elevation. We concluded that the poly‐cistronic expression of CNROE induced partial reprogramming into photoreceptor cells. We hypothesize that the direct reprogramming into photoreceptor cells might require relatively high protein expression levels of transcriptional factors.